PROSEDUR PENGUJIAN AUDIT SUBSTANTIF ATAS AKUN KAS DAN BANK PT. PQR OLEH KANTOR AKUNTAN PUBLIK JOACHIM ADHI PITER POLTAK DAN REKAN - Indira Pramudita Al Driani, (2023)
The purpose of this final project is to explain the methods and procedures of substantive testing conducted in the examination of cash and bank by Joachim Adhi Piter Poltak & Partners Public Accountants Office, in order to detect the effectiveness and adequacy of internal controls related to the management of cash and banking transactions owned by PT. PQR. Information and data were obtained through observation related to the stages conducted during substantive audit testing for cash and bank accounts owned by PT. PQR, interviews with one of the auditor staff members at Joachim Adhi Piter Poltak & Rekan Public Accountants Office, as well as documentation of the necessary audit evidence for cash and bank accounts. The stages of substantive audit testing conducted included the preparation of cash and bank audit working papers, physical cash examination, bank reconciliations, and controls over bank confirmations. The results of this testing indicate that the presentation of cash and bank accounts owned by PT. PQR has met the reasonable criteria and is in accordance with the applicable accounting standards in Indonesia.